A Review Study on Nutritional and Medicinal Importance of Lemon (International Journal of Innovative Research in Computer Science & Technology, 2021)
For millennia, experts have paid close  attention to a tiny evergreen shrub known as a lemon because  it has such a magical and mystical significance. It is not only  utilized as a food source, but it also has therapeutic and  nutritional value. According to nutritionists, eating instead of  taking medication improves the odds of long-term healing or reduces the risks of adverse effects. Lemon plants are known  for their thorny branches and white blooms with purple  borders. Citrus lemon has anti-cancer properties, as well as  the ability to prevent kidney stones. Bring a fever to a halt  and restore ph balance. Citral, limonene, terpineol, geranyl  acetate, and linalyl are phytochemicals found throughout the  entire plant. Similarly, if people start their day with lemon, it  reduces fat and cleanses the digestive systems; if people apply it to their skin, people will have the most lustrous or acne-free skin ever. If people drink it with honey, it will  assist to alleviate sore throats, constipation, or a variety of  other ailments. In summary, it is beneficial to people of all  ages and genders, from tiny bee stings to big kidney stones.
Keywords: Cancer; Hypertension; Lemon; Nutrition; Obesity